PENGARUH INTERVENSI BERBASIS PENDEKATAN MONTESSORI TERHADAP PENURUNAN SKOR DEPRESI ORANG LANSIA DI PSTW C - Laura Jane Henriette Ajawaila; Elmira N. Sumintardja (MANASA, 2015)
Fast growing of elderly population in Indonesia has not been met with a decent living. Elderly people susceptible to depression related to health deterioration and living in a nursing home (lost of family, home, and freedom). Symptoms of depression include physical complaints, lack of vigour, feelings of guilt, low sense of self-worth, and withdrawal from social environment. Lack of physical and cognitive activity can worsen the condition of elderly people. Elderly people in PSTW C only have self-care activity. Researcher develops Montessori-approach-based intervention (MABI) to encourage elderly people to be involved in activities so they can feel positive emotions and be helpless. A quasi-experimental study with before-and-after design to find whether MABI can lower depression scores of elderly people living in PSTW C. Research instruments are adapted Geriatric Depression Scale-Short Form (GDS-SF), adapted The Modified Mini Mental State (3MS) and Senior Apperception Technique (SAT). MABI are made based on a need of analysis (being valued, accompanied, and cared for) and consist of 8 sessions (2x1 week, @30 minutes/session). MABI was evaluated by observation, mood evaluation, interview, and examination of adapted GDS-SF (pre-post test). The number of participants of this study were 7 elderly women with depression or possible depression and disabilities (stroke, diabetes, leg fractures, chest thightness).There is a decrease in participants’ depression scores. Average calculation of intervention evaluation was 80.8% (≥75%). MABI gives effect on decreasing depression scores (depressive symptoms reduced) on participants temporarily.